2021
DOI: 10.3390/ijms22115456
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of microRNA in Periodontitis: Pathophysiology, Clinical Potential and Future Molecular Perspectives

Abstract: During the last few decades, it has been established that messenger ribonucleic acid (mRNA) transcription does not inevitably lead to protein translation, but there are numerous processes involved in post-transcriptional regulation, which is a continuously developing field of research. MicroRNAs (miRNAs) are a group of small non-coding RNAs, which negatively regulate protein expression and are implicated in several physiological and pathological mechanisms. Aberrant expression of miRNAs triggers dysregulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 119 publications
2
50
0
Order By: Relevance
“…Wang et al 30 showed that upregulation of miRNA‐185‐5p inhibited osteoclast differentiation and bone resorption. Recent studies have also reported that miRNAs are involved in the development of periodontal disease, especially the process of alveolar bone destruction 31 . In the pathogenesis of periodontitis, dysregulated miRNAs such as microrornaslet‐7a, miR‐125b, miR‐100, and miR‐21 have been reported 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al 30 showed that upregulation of miRNA‐185‐5p inhibited osteoclast differentiation and bone resorption. Recent studies have also reported that miRNAs are involved in the development of periodontal disease, especially the process of alveolar bone destruction 31 . In the pathogenesis of periodontitis, dysregulated miRNAs such as microrornaslet‐7a, miR‐125b, miR‐100, and miR‐21 have been reported 32 .…”
Section: Discussionmentioning
confidence: 99%
“…miRNA-mediated deregulation of gene expression is likely to be a key molecular mechanism linking periodontitis with systemic diseases [ 25 ]. The genes with the highest degrees in shared-DEminRNA-gene network included PTEN, CCND1, MDM2, SCD, and TNRC6A, and these may be important miRNA-deregulated mediators linking H. pylori infection and periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies using multiple large datasets with comprehensive metadata are essential. An important caveat is that deregulated exosomal or circulatory miRNA was not analyzed in the present investigation, and these may be more important in the pathogenic mechanisms linking periodontitis with systemic disease [ 25 ]. In addition, future studies may address deregulated, genes, or other noncoding RNAs as linkage mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, saliva has been studied thoroughly as a potential diagnostic tool because its collection is non-invasive and economical. Salivary miRNA expression is modulated by various systemic diseases [ 15 ].…”
mentioning
confidence: 99%